1992
DOI: 10.1007/bf00308832
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive repeat liver resection for hepatic metastases of colorectal carcinoma

Abstract: Although hepatectomy for liver metastases from colorectal carcinoma is an effective treatment, recurrence in the liver is still the most common site after hepatectomy. Thirty patients underwent hepatectomy for hepatic metastases and 17 of them had recurrence in the remnant liver during the following 12-year period. Six of the 17 patients underwent a removal of isolated hepatic recurrences. Two of the six patients underwent a third hepatectomy, and three patients underwent partial lung resection on a total of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 13 publications
2
20
0
2
Order By: Relevance
“…In 2004, two studies showed that the addition of targeted therapies increased the objective response rate and the progression-free period [42,43]. Nevertheless, 50% to 70% of patients eventually develop a recurrence after hepatectomy; recurrence is isolated within the liver in a third of cases [37,40,44,45]. Surveillance in anticipation of liver recurrence must be a constant concern in the management of patients with liver metastases from CRC.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, two studies showed that the addition of targeted therapies increased the objective response rate and the progression-free period [42,43]. Nevertheless, 50% to 70% of patients eventually develop a recurrence after hepatectomy; recurrence is isolated within the liver in a third of cases [37,40,44,45]. Surveillance in anticipation of liver recurrence must be a constant concern in the management of patients with liver metastases from CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies found that the median survival with recurrent colorectal metastases to the liver ranged from 16 to 46 months after repeat hepatectomy. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] On the other hand, the median survival of patients with unresectable recurrence after first hepatectomy was only 5-14 months. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] A comparison of resection results with historical findings on unresectable liver metastases strongly suggests that survival could be prolonged by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the incidence of postoperative complications after second hepatectomy (22%) was not significantly higher than that after first hepatectomy (11%). Other studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] have reported complication rates ranging from 15% to 52%. Pinson et al reported that the most common complications were hemorrhage, pleural effusion, abscess formation, pneumonia, biliary leakage, biliary stenosis, and transient hepatic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Even if it is reasonable that these variables affect survival, they are of limited utility in the daily clinically practice. The use of only these variable does not allow to stratify the long-term outcome especially in the current era of modern and efficient SC (15,28,29). Similar considerations may be done for the histopathologic features, such as fibrous pseudocapsule formation, the degree of fibrosis around the metastases, single-versus confluent-node growing, infiltrative versus expansive type of growth, and invasion of intrahepatic vascular structures (30)(31)(32).…”
Section: Carcinoembryonic Antigenmentioning
confidence: 99%